Interaksi lisan dalam pengajaran dan pembelajaran Bahasa Melayu - Jamian, Abdul Rasid; Othman, Shamsudin; Ishak, Sufiza (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2013)
Teachers' abilities in performing teaching and learning depends on the selection of teaching strategies. Teachers also need to be wise in selecting appropriate techniques, methods, and approaches. The impact of teaching depends on all the elements that are used by teachers to stimulate and encourage students to think critically and creatively, thus being able to communicate and interact effectively. This study aims to identify the form of verbal interaction frequently used by Malay Language teachers in teaching and learning activities in the classroom. The study samples are of 113 teachers from 13 mainstream secondary schools in the rural areas in Kluang, Johor. Data were analyzed by using the Statistical Package for the Social Sciences (SPSS) version 16.0. The findings showed the mean of 2.78 (SD = 0.42) for verbal interaction initiatives frequently used by teachers during teaching and learning of the Malay Language. This is followed by a form of verbal interaction that is often used by teachers while delivering information with the mean of 2.88 (SD = 0:47), while the form of verbal interaction that is often used by teachers when giving instructions showed the mean of 2.68 (SD = 0.49), and the form of verbal that is used by teachers to end classes denotes the mean of 2.67 (SD = 0.49). Finally, this study shows the average mean and the verbal interaction between teachers and students is best when the use of strategies, methods, techniques, and approaches are appropriate.